Students perception on GST: a study on Swinburne University and UiTM Samarahan / Nabila Hana Morshidi and Alysha Anuar - Morshidi, Nabila Hana; Anuar, Alysha (2014)
This chapter focuses on the background ofthe study which is the perception towards GST among students from public and private universities that is UiTM Samarahan and Swinburne University. This chapter will discuss the background of the study and also describe the problem statement along with the research questions. Research objectives are listed based on the research questions. Moreover, this chapter will too explain the information regarding the scope of study. Significance of the study is discussed as well and towards the end of the chapter, explanation on the definition of terms and concepts related to the study will be described.